Towards the interoperability of spontaneous reporting systems in pharmacovigilance : a maturity model approach with a sociotechnical system focus - Schurer, Maximillian Juan (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.